SANGGIT TOKOH DALAM BANJARAN SENGKUNI - YB Rahno Triyogo (Institut Seni Indonesia Surakarta, 2018)
Banjaran Sengkuni is a play that tells about the life journey of a character named Sengkuni. Through the play the puppeteer believes that the character’s character is formed not only from birth, but also from the process of the fetus through sexual intercourse by both parents. Unless formed since in the womb, it will also be formed by the environment that surrounds it. What is meant by the environment includes the family environment, the surrounding community, and the universe. The character of Sengkuni in Banjaran Sengkuni is very determined by the process of the occurrence of a baby or fetus in the womb, which is through the process of adultery that is culturally considered negative even sin. He inherited his father’s character, namely a gandarwa named Setibar. The thing that signifies the character that can be observed is that Sengkuni’s baby despite being born in a handsome face but he fuses like a fangled father. In the tradition of canine puppet reflects a negative value.Keywords: character, fetus, environment, universe